ANALYSIS OF THE EFFECTIVENESS OF FAST SECURE CREDIT (KCA) AT PT. PENGADAIAN (PERSERO) RANTEPAO BRANCH - Jesica Pongringgi; Dina Ramba; Jemi Pabisangan Tahirs (CV. Four Son Scholarship, 2023)
The aim of this research is to determine the effectiveness of fast safe credit (KCA) distribution at PT. Rantepao branch pawnshop. The method used in this research is qualitative. The data sources used in this research are primary data and secondary data, where primary data is data obtained directly from original sources or first parties, and primary data is specifically collected by researchers to answer research or research questions. The results of this research show that the effectiveness of fast safe credit (KCA) distribution has been running effectively. It can be seen from customer satisfaction in fast safe credit (KCA) services starting from the customer's response to the application and disbursement process, the benefits received and the security provided as well as information. Analysis of the effectiveness of fast safe credit distribution (KCA) at PT. Pegadaian (Persero) Rantepao Branch. The aim of this research is to determine the effectiveness of fast safe credit (KCA) distribution at PT. Rantepao branch pawnshop. The method used in this research is qualitative. The data sources used in this research are primary data and secondary data, where primary data is data obtained directly from original sources or first parties, and primary data is specifically collected by researchers to answer research or research questions. The results of this research show that the effectiveness of fast safe credit (KCA) distribution has been running effectively. It can be seen from customer satisfaction in fast safe credit (KCA) services starting from the customer's response to the application and disbursement process, the benefits received and the security provided as well as information